A Christian Perspective on Belonging: A Case Example of a Gentrifying Urban Neighborhood - Starkenburg, Keith (Christian scholar's review, 2018)
When neighborhoods gentrify, residents can be physically displaced as well as psychologically displaced. This psychological displacement can occur even if the resident is not physically displaced. In this article, Keith E. Starkenburg and Mackenzi Huyser explore the significant impact that neighborhood changes have on one’s attachment to place as expressed through the concept of Christian belonging. They develop a theology of place, rooted in Christian perspectives on belonging, that informs thoughtful conversation and action in gentrifying neighborhoods.